EXPERIENCES AND CURRENT STATUS OF FORMING PROFESSIONAL COMPETENCE AND CREATIVITY OF EDUCATORS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the professional competence and creativity level of educators working in the preschool education system, as well as foreign and local experiences of their formation. The professional competence of an educator includes not only knowledge and skills, but also problem-solving skills, creativity and innovative approaches. The article compares the experience of countries such as Finland, Japan, Germany, South Korea with the practice of Uzbekistan. The importance of methodological training, digital technologies and individual approaches in developing creative competence is highlighted. At the same time, existing problems, opportunities and proposals in Uzbekistan are also described. The article offers a systematic approach aimed at increasing the professional and creative potential of educators.